ORGANOLEPTIC EVALUATION OF FRESH COW MILK FORTIFIED WITH LEMONGRASS POST PASTEURIZATION - H. M, SIAHAAN; SUMERTA, I N. S.; LINDAWATI, S. A. (Majalah Ilmiah Peternakan, 2021)
The study to the effect of lemon grass fortification on organoleptic and pH of pasteurized milk. The design used a Completely Randomized Design (CRD) with four treatments and four replications. The treatments were: P0 = pasteurized milk without lemon grass (control), P1 = pasteurized milk + 5% lemon grass, P2 = pasteurized milk + 10 lemon grass, and P3 = pasteurized milk + 15% lemon grass. The variables observed were: color, taste, aroma, thickness and pH. The results showed that the preference value for color at P0 was significant (P<0.05) with P1 and P3, but P1, P2, and P3 were not significant (P>0.05). Preference for pasteurized milk taste at P0 was significant (P<0.05) with P2, but P1, P2, and P3 were not significant (P>0.05). Preference for the aroma at P0 was significant (P<0.05) with P3, but P1, P2, and P3 were not significant (P>0.05). Preference for the thickness at P0, P1, P2, and P3 were not significant (P>0.05). The pH value of pasteurized milk ranged from 6.54 to 6.64. It can be concluded that lemon grass fortification until the level of 15% was affected on aroma and pH, but not effect on color, taste, and thickness of pasteurized milk.